A hybrid small‐diameter tube fabricated from decellularized aortic intima‐media and electrospun fiber for artificial small‐diameter blood vessel. Issue 5 (18th February 2019) - Wu, Pingli; Nakamura, Naoko; Morita, Hiroko; Nam, Kwangwoo; Fujisato, Toshiya; Kimura, Tsuyoshi; Kishida, Akio
Abstract: Hybrid small‐diameter tubes were fabricated by wrapping decellularized aortic intima‐media sheets around a tubular stainless steel mandrel with diameter 4 mm, and then by coating with electrospun segmented polyurethane. The synthetic coat was deposited uniformly to a thickness of about 0.5–3.5 μm depending on the duration of electrospinning. Resistance to luminal pressure, burst strength, and stiffness increased with the thickness of the electrospun coat, suggesting that the synthetic fabric reinforces the reconstructed acellular aortic intima‐media. Human umbilical vein endothelial cells seeded on the inner surface acquired flagstone morphology, while normal human dermal fibroblasts seeded on the outer surface proliferated well and partly migrated into deeper layers. Collectively, the data suggest that reinforcing decellularized aortic intima‐media with electrospun fibers generates a small‐diameter hybrid blood vessel with good biocompatibility and suitable mechanical properties. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1064–1070, 2019.